1996
DOI: 10.1007/s002530050732
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production by a mixed culture of flocculent strains of Zymomonas mobilis and Saccharomyces sp.

Abstract: Pure and mixed cultures of Zymomonas mobilis and Saccharomyces sp. were tested for the production of ethanol using sucrose as the carbon source. Both strains, isolated from spontaneously fermenting sugar-cane juice, are flocculent and alcohol-tolerant. The best results were obtained using a mixed culture, with a yield of 0.5 g ethanol/g sugar consumed and a volumetric productivity of 1.5 g ethanol l-1 h-1. No levan was produced even if a sucrose-based medium was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…These results clearly demonstrated that starch saccharification potential of S. diastaticus was higher than that of R. stolonifer and A. terreus. Similar results have been reported by Abate et al (1996).…”
Section: Fermentation Using a Terreus And Z Mobilissupporting
confidence: 92%
See 1 more Smart Citation
“…These results clearly demonstrated that starch saccharification potential of S. diastaticus was higher than that of R. stolonifer and A. terreus. Similar results have been reported by Abate et al (1996).…”
Section: Fermentation Using a Terreus And Z Mobilissupporting
confidence: 92%
“…The supernatant obtained by centrifugation of the culture broth at 6,000 ×g was used for reducing sugars (Miller, 1959) and ethanol (Caputi et al, 1968) analyses. The kinetic parameters of ethanol fermentation were calculated according to Abate et al (1996).…”
Section: Methodsmentioning
confidence: 99%
“…The microbial biomass was determined by harvesting cells by centrifugation, drying them at 70°C under vacuum to a constant weight, and expressed as gram dry cell weight (DCW) per liter [27]. The kinetic parameters of ethanol fermentation were determined followed by Abate et al [28] as follows:…”
Section: Estimationsmentioning
confidence: 99%
“…For examples, Abate et al (1996) described ethanol production by a co-culture of Z. mobilis and Saccharomyces sp. with higher yields and production rates than with either microorganism in pure culture.…”
Section: Introductionmentioning
confidence: 99%